Amniotic fluid-derived stem cells demonstrate limited cardiac differentiation following small molecule-based modulation of Wnt signaling pathway. (18th March 2015) - Connell, Jennifer Petsche; Ruano, Rodrigo; Jacot, Jeffrey G
Abstract: Amniotic fluid-derived stem cells (AFSC) are a promising cell source for regenerative medicine and cardiac tissue engineering. However, a non-xenotropic differentiation protocol has not been established for cardiac differentiation of AFSC. We tested a small molecule-based modulation of Wnt signaling for directed cardiac differentiation of AFSC. Cells were treated with inhibitors of glycogen synthase kinase 3 and Wnt production and secretion in a time-dependent and sequential manner, as has been demonstrated successful for cardiac differentiation of embryonic and induced pluripotent stem cells. Cells were then analyzed for gene and protein expression of markers along the cardiac lineage at multiple days during the differentiation protocol. At the midpoint of the differentiation, an increase in the percentage of AFSC expressing Islet-1, a transcription factor found in cardiac progenitor cells, and Nkx-2.5, a cardiac transcription factor, was observed. After a 15 d differentiation, a subpopulation of AFSC upregulated protein expression of smooth muscle actin, myosin light chain-2, and troponin I, all indicative of progression down a cardiac lineage. AFSC at the end of the differentiation also demonstrated organization of connexin 43, a key component of gap junctions, to cell membranes. However, no organized sarcomeres or spontaneous contraction were observed. These results demonstrate that small molecule-based modulation of Wnt signaling alone is not sufficient to generate functional cardiomyocytes from AFSC, though an upregulation of genes and proteins common to cardiac lineage cells was observed.